Gas chromatographic validated method for quantification of ayurvedic polyherbal formulation - Saini, Mr. Navdeep (Asian Journal of Pharmaceutics (AJP), 2015)
Anew gas chromatographicâ€flame ionization detector (GCâ€FID) method was developed for quantification of ayurvedicÂ polyherbal formulation.The GCâ€FID method was found highly accurate, sensitive, simple and precise.This method wasÂ validated as per international conference on harmonization (ICH) guidelines. Experimental work was performed by nonpolarÂ capillary column (Zbâ€5, 5%â€Phenylâ€95%â€dimethylpolysiloxane). Film thickness of capillary column (Zbâ€5) was (0.25 Î¼m)Â and length 30 m Ã— 0.25 mm i.d. The temperature of the oven, injector and detector were 200, 210 and 280Â°C respectively.Â Data processing system was applied to obtain data. The standards and test samples were prepared in absolute ethanol. TheÂ principle constituents tâ€Anethol, dâ€Limonene, cuminaldehyde and thymol were found in ayurvedic polyherbal formulation.The ICH validation parameters for the proposed procedure, recovery (limit 98.85â€“100.76%), precision (<1.00%), limitsof detection, limits of quantification and linearity (r2 = 0.995 Â± 0.002) were observed under acceptance limit. ValidationÂ results were statistically calculated.The result shows that method is selective and reproducible for quantification of ayurvedicÂ polyherbal formulation. The presented GC method can be applied for the routine analysis of principle constituents as well as ayurvedic polyherbal formulation. Key words: Gas chromatography, international conference on harmonization, polyherbal formulation, validation